PENGEMBANGAN PENDIDIKAN NASIONAL BERBASIS BUDAYA LOKAL - Richa Dewi Rahayu (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2021)
In this world there are hundreds or even thousands of cultures, races, tribes, languages and countries. Through education we are not only given lessons and knowledge about our own language, ethnicity, race, religion, culture and spirit but also race, ethnicity, language, other countries, the goal is that we can know other ethnicities, languages, cultures, countries so that we can interact not only with people in our own country but with people in other countries by establishing good relationships with other countries in the form of cooperation in the fields of economy, education and so on.Key words: Educational development, based on culture